Bradykinesia Is Driven by Cumulative Beta Power During Continuous Movement and Alleviated by Gabaergic Modulation in Parkinson's Disease - Prokic, Emma J.; Stanford, Ian M.; Woodhall, Gavin L.; Williams, Adrian C.; Hall, Stephen D. (Frontiers in Neurology, 2019)
Spontaneous and ‘event-related’ motor cortex oscillations in the beta (15-30Hz) frequency range, are well established phenomena. However, the precise functional significance of these features is uncertain. An understanding of the specific function is of importance for the treatment of Parkinson’s disease (PD), where attenuation of augmented beta throughout the motor network coincides with functional improvement. Previous research using a discrete movement task, identified normalisation of elevated spontaneous beta and post-movement-beta-rebound following GABAergic modulation. Here we explore the effects of the GABA-A modulator, zolpidem, on beta power during the performance of serial movement in seventeen (15M, 2F; mean-age 66±6.3 years) PD patients, using a repeated-measures, double-blinded, randomised, placebo-control design. Motor symptoms were monitored before and after treatment, using time-based Unified Parkinson’s Disease Rating Scale measurements and beta oscillations in primary motor-cortex (M1) were measured during a serial-movement task, using magnetoencephalography. We demonstrate that a cumulative increase in M1 beta power during a 10s tapping trial is reduced following zolpidem, but not placebo, which is accompanied by an improvement in movement speed and efficacy. This work provides a clear mechanism for the generation of abnormally elevated beta power in PD and demonstrates that peri-movement beta accumulation drives the slowing, and impaired initiation, of movement. These findings further indicate a role for GABAergic modulation in bradykinesia in PD, which merits further exploration as a therapeutic target.